Review of wire-mesh tomography in different experiments - Rajan, Navintiran; Ruzairi, Abdul Rahim; Mohd Shukri, Manaf; Mohd Hafiz, Fazalul Rahiman; Anita, Ahmad; Yusri, Md Yunus; Sallehudin, Ibrahim; Mimi Faisyalini, Ramli; Yasmin, Abdul Wahab; Suzanna, Ridzuan Aw Abdullah (Malaysian Society for Computed Tomography and Imaging (MyCT), 2021)
Wire-mesh tomography is completely new to the tomography field. First founded in 1998, the wire-mesh tomography had been used in several sectors as secondary optional sensors. This sensor can be used to gain void fraction distribution in multiphase flow visualization. By using tomography techniques, several measurements like velocity or phase fraction boundaries can be determined and analysed. The sensor basically built perpendicularly as transmitter and receiver layer located above and below respectively. With wires made of tinned copper and 16 sensors for each layer, the tomography is considered low-cost, easy built and can sustain in a harsh environment to investigate multiphase flow. As an instantaneous tomography method, wire-mesh tomography has advantage in speed but has less image resolution because classic wire-mesh tomography image reconstruction methods only provide same amount of pixels as measurement number. In order to increase image resolution, anew image reconstruction method based on sensitivity map is proposed, which is of providing more pixels (sub pixels) by solving inverse problem with capacitive wire-mesh tomography image reconstruction. The image reconstruction algorithms, including the traditional wire-mesh direct image reconstruction algorithm, the linear back projection, the projected Land weber iteration, and the total variation based iteration, are conducted and the results are compared each other